Conventional wood drying simulation using CVFEM - Salinas, Carlos; Chávez, Cristian; Gatica, Yerko; Ananias, Rubén (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
The main objective of the present work is the development of an original two-dimensional numerical simulation of wood drying, based on the water potential concept using the Control Volume Finite Element Method (CVFEM). The mathematical model was based on a set of non-linear second partial differential equations, which were solved by a numerical procedure using CVFEM. Results of drying curves and isoconcentrations are shown for aspen (Populus tremuloides) sapwood and compared with numerical and experimental data. Furthermore, the impact of the variation of various numerical parameters was studied to evaluate the algorithms consistence. It had been concluded that the current numerical method was consistent and allows to simulate wood drying satisfactorily resulting in detailed information about wood moisture content distribution.